2019
DOI: 10.1177/1066480719893964
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Intensive Parenting Attitudes and Gender Norms Among U.S. Mothers

Abstract: Motherhood is a time of significant change for a woman. Once a woman enters motherhood, she must then navigate her mothering role within the societal expectation of intensive mothering. Intensive mothering prescribes the right way to be a mother which places unrealistic standards on mothers, which can lead to negative emotional reactions. A better understanding of intensive mothering may aid in mothers’ ability to navigate the unrealistic expectations. This study sampled 525 mothers within the United States an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 23 publications
2
51
1
2
Order By: Relevance
“…This shift in responsibility potentially magnified beliefs that mothers needed to be the essential parent. Our data analysis showed that as COVID-19 continued and cases started increasing, initially, Essentialism scores decreased back to levels found prior to COVID-19 (Forbes et al, 2019 ). This was not related to any point in time, but rather the case count for a given state based on when the parent’s response was recorded.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This shift in responsibility potentially magnified beliefs that mothers needed to be the essential parent. Our data analysis showed that as COVID-19 continued and cases started increasing, initially, Essentialism scores decreased back to levels found prior to COVID-19 (Forbes et al, 2019 ). This was not related to any point in time, but rather the case count for a given state based on when the parent’s response was recorded.…”
Section: Discussionmentioning
confidence: 48%
“…Similarly, no significant differences existed for Stimulation on either ethnicity, region, education level, or child’s age. Previous studies also found few differences in intensive parenting attitudes across demographics (Forbes et al, 2019 ). This seems to indicate that gendered parenting attitudes in the U.S. are somewhat dominant across parent groups.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One study did find that young adults who perceived their mothers emphasized femininity traits were more likely to be prone to anxiety, whereas maternal overprotection was associated with lowered adjustment (Shevenell & Meteyer, 2018). In the era of intensive mothering, characterized by extensive expenditure of time and energy resources (Hays, 1996), mothers across a broad range of demographic profiles experience the pressure to live up to society’s expectations of the ideal mother (Forbes et al, 2020). Single mothers may feel extreme pressure to live up to society’s gendered ideal of the perfect mother.…”
Section: Single-parent Households: Challenges Gender and Emerging Amentioning
confidence: 99%
“…Not only will less helicoptering be beneficial to the parent in terms of delegating energy via fostering autonomy, but it will impact the well-being and self-efficacy of the young adult children of single parents. Mothers put a lot of pressure on themselves in attempting to live up to the ideal created by societal expectations (Forbes et al, 2020). For single mothers, this pressure may be even more salient.…”
Section: Implications For Practicementioning
confidence: 99%